Evidence available to guide care during labor and birth for women and their partners who know their baby will be stillborn: a scoping review protocol. Issue 8 (10th August 2021) - Knight, Alissa; Pollock, Danielle; Boyle, Fran; Horey, Dell; Warland, Jane
ABSTRACT: Objective: The aim of the proposed scoping review is to explore and summarize the range of available evidence for bereavement care, specifically in relation to labor and birthing experiences of a stillborn baby. Introduction: Clinical practice guidelines for bereavement care following pregnancy loss have been developed. However, there remains a lack of evidence to guide recommendations for providing appropriate care to parents at the time of diagnosis, and during the labor and birth of a stillborn baby. Inclusion criteria: The proposed review will consider studies, reports, guidelines, evidence syntheses, and other relevant literature that explore the experiences, needs, and care provided to bereaved parents during labor and birth of a stillborn baby. Methods: The search strategy for the proposed scoping review will aim to locate both published and unpublished documents, using a three-step search strategy. An initial search will be conducted using the databases MEDLINE and CINAHL to identify relevant articles; a second search will be conducted across all included databases, incorporating identified keywords and index terms; and finally the reference lists of included studies will be screened for additional sources. Google Scholar and Web of Science will be searched for relevant gray literature. The search will restrict documents from 2000 to present to maintain clinical relevancy. Only studies published in English will be included. Results of the search will be exported into a template, where data will be categorized using five key domains (communication, recognition of parenthood, effective support, shared decision-making, and organizational response) summarized into positive, negative, or neutral outcomes, and further refined into common issues across these domains. Scoping review registration: Open Science Framework "birthing in grief: a scoping review" https://osf.io/xw9md